PENGEMBANGAN E-LKPD BERBANTUAN APLIKASI LIVEWORKSHEETS PADA MATERI WUJUD ZAT DAN PERUBAHANNYA - Restu Nurfadila; Akhmad Nugraha; Agnestasia Ramadhani Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research examines the development of interactive multimedia teaching materials that are very relevant to today's learning needs. The development of E-LKPD teaching materials uses the live worksheets application to make learning more interesting and interactive. The aim of this development is to create E-LKPD using the live worksheets application so that learning becomes more varied and interactive for students. This development was carried out using the R&D (Research & Development) method adapting the ADDIE model with stages of analysis, design, development, implementation and evaluation. The research instruments used include observation, interviews, documentation and questionnaires. The product developed was validated by material experts, media experts and language experts to assess its validity before being implemented in elementary schools. The validation results show a score of 78% from material experts (decent), 75% from language experts (decent), and 96% from media experts (very decent), with an overall average score of 86.5%, included in the very decent category. . Thus, the E-LKPD product assisted by the liveworksheets application has met the valid criteria and is suitable for implementation in grade 4 elementary schools.